Chapter How Italians coped with COVID-19 lockdown: evidence from a survey promoted through social networks - Bellide, Riccardo (Proceedings e report, 2023)
During the first wave of the pandemic, a quantitative study was implemented through an online survey on the SEBCOV study in five countries: Italy, Slovenia, Malaysia, Thailand, and the United Kingdom. Its objective consisted of investigating the social, ethical, and behavioral aspects of the COVID-19 pandemic. In this work, we focus on the analysis of Italian data coming from a survey promoted through social networks and carried out through two different sampling designs. The two samples present sociodemographic characteristics different from each other and from the whole Italian population, thus producing distorted results without the use of weights. Sample weights have been created through post-stratification and raking. The study participants were adults who had given their informed consent, who resided in Italy and who were able to use a computer or smartphone. Even before the first government decree-law, almost half of the Italian population had already changed their behaviour in order to protect themselves and limit the spreading of the virus. Among them, around 10% moved to a different house looking for company during the lockdown period. Indeed, one of the most worrying aspects was the limitation of social interactions together with mental health, with some differences between age classes and gender. Almost all respondents declared that they had spent the lockdown period connecting with other people through the social network that had a fundamental role in this challenging period, for all age classes. The strong influence of Internet on everyday life during this period helped to keep people close but also encouraged the spreading of fake news, indeed almost all respondents received fake news on different topics. Despite all the problems faced by the Italian population during the quarantine period, hope messages are still present in the final optional open-ended question that provides non-structured but precious qualitative information.